THE IMPLEMENTATION OF MATCHING GAMES TO IMPROVE INDONESIAN LEARNING OUTCOMES FOR THE FIRST-GRADE STUDENTS AT SDN 1 CRJ - Niken Yulianah; Winarsih; Uswati Solehah; Endang Sri Maruti; Nico Irawan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
The low Indonesian learning outcomes of the first-grade students at SDN 1 CRJ is caused by the implementation of teacher-centered learning methods like the lecture method. To overcome it, the Classroom Action Research in this paper applies the Matching Games game method to students. This paper reports an improvement of students’ learning outcomes in reading and writing Indonesian learning subjects in chapter 5 of